Onlay Technique in Incisional Hernia Repair—A Systematic Review - Köckerling, Ferdinand (Frontiers in Surgery, 2018)
Introduction A meta-analysis that compared the onlay versus sublay technique in open incisional hernia repair identified better outcomes for the sublay operation. Nonetheless, an Expert Consensus Guided by Systematic Review found the onlay mesh location useful in certain settings. Therefore, all studies on the onlay technique were once again collated and analyzed. Material and Methods A systematic search of the available literature was performed in August 2018 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library. For the present analysis 41 publications were identified as relevant. Results In five prospective randomized trials and 17 observational studies the postoperative complication rates ranged between 5% and 76%, with a mean value of 33.5%. The recurrence rates in these studies also ranged between 0% and 32%, with a mean value of 9.9%. Hence, compared with the literature data on the sublay operation, more postoperative complications, in particular wound complications and seroma, with a comparable recurrence rate, were identified. Conclusion When the onlay technique is used in certain settings for incisional hernia repair, an careful dissection technique and prophylactic measures (drainage, abdominal binders, fibrin sealant) should be employed to prevent wound complications and seroma formation.